Coronary CT Angiography with Use of Iterative Reconstruction Algorithm in Coronary Stenting: A Systematic Review of Image Quality, Diagnostic Value and Radiation Dose - Shammakhi, A.; Sun, Zhonghua (American Scientific Publishers, 2015)
The aim of this study was to perform a systematic review of the image quality, diagnostic value and radiation dose of coronary CT angiography with use of iterative reconstruction (IR) in the assessment of coronary stents when compared to the standard filtered back-projection (FBP) techniques. A search of medical databases of English literature was performed to identify studies comparing coronary CT angiography with use of IR and FBP techniques in coronary stenting. Qualitative and quantitative assessment of image quality, diagnostic accuracy and radiation dose associated with coronary CT angiography were analyzed and compared between the two reconstruction algorithms. Ten studies met selection criteria and were included in the analysis. In comparison with FBP, coronary CT angiography with use of IR showed improvement in image quality through both qualitative and quantitative analysis. The IR technique resulted in higher diagnostic value than that of FBP with the mean sensitivity, specificity and accuracy being 98%, 77.4% and 80.1% for IR technique, and 90.5%, 68.2%, and 68.6% for FBP approach, respectively, with significant difference reached in the specificity and accuracy (p <005). Furthermore, there was significantly lower dose with use of IR compared to FBP technique (4.4 mSv vs. 7.0 mSv). Coronary CT angiography with use of IR algorithm leads to significant improvements in the assessment of coronary stents with much lower radiation dose.